The unconscious in the study of human interaction (Psicologia USP, 1991)
This report shows the necessity of enrolling the subject about Social Psychology in the most extensive tradition of the subject matter, which is established according to Gestalt School, in Kurt Lewin's theory, which allow it to be conceived in its totality, and complexity that has not been done by some dominant tendencies in the Brazilian Social Psychology. The work brings the proposal of valorization of the unconsciousness in the study of the human interaction, which pressuposes an included subject for the Social Psychology. Without this subject il is not possible to lay down theories which can contain in their swelling the establishment of the relations between the individual destination and the society destination, the comprehension of the social life through the participation of the psychological and concrete subjects that inhabit their structures. This proposal takes to a conception of object of the Social Psychology laid down in the tradition in which we are in and also allow us to put it in harmony with Psychoanalysis, reaching a model of epistemic subject in Social Psychology. It indicates a way to an exam of affective exchange, implicit in the Psychological Interaction where the unconsciousness acquires an important role and to make possible an ideal of mental health.